Sustainable Nature Therapy in Inclusive Educational Environments: Research Findings and Methodological Recommendations - Danylchuk, Larysa; Raievska, Yana; Yurkiv, Yaroslava; Levitsky, Vadim; Stynska, Viktoriia; Krasnova, Nataliia; Kravchyna, Tetiana (European Journal of Sustainable Development, 2025)
The article presents an empirical study on the use of nature therapy in inclusive educational environments in Ukraine. It highlights the prevalent use of plant and color therapy, while zootherapy and sand therapy are less applied. The research underscores discrepancies between the theoretical endorsement and actual practice of nature therapy, with gender-specific tendencies and urban-rural differences. The study concludes that educators need updated scientific and methodological resources to effectively integrate nature therapy. Future research should focus on developing effective strategies for broader application in inclusive settings. Keywords: Inclusive Educational Environment, Therapy, Children with Special Educational Needs.